ANALYZING THE CUSTOMER BONDING OF THE PRIME CLINIC CUSTOMERS IN MANADO - Rende, Gabriella; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: Customer bonding is, just as the term implies, the process through which a company or organization makes connections with its customers. The goal of customer bonding to develop a relationship and sense of community, including the customers so that they: Feel welcomed, are more likely to continue patronizing the company (and its products or service) are more likely to recommend the company to friends and family. By engaging in customer bonding, companies are able to generate a sense of loyalty and boost its revenue, In order to achieve the objectives, the researcher got information from 15 informants, and this research using a qualitative study which is an in-depth interview in order to get a clear data and uses purposive sampling to arrange the answer from the informants. Based on the data analysis and discussion, the conclusion of this research can be concluded that Customer bonding is the result of the engagement between the customer and the Clinic. Customer bonding (Awareness and Relationship); comes from the customer experiences such as a good experience, positives results, and most importantly it causes by the positive outcomes that the customer has been through when visiting The Prime Clinic. Customer bonding can comes naturally when the customer feels happy, feels satisfied with the services.Keywords: Customer Bonding, Awareness, RelationshipÂ